1976
DOI: 10.1055/s-0028-1093620
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Streptozotocin Diabetes on Adrenal Function in Male Rats

Abstract: Male Wistar rats were treated with an i.v. dose of 100 mg/kg of Streptozotocin (STZ). Either 5 days or 1, 2 or 3 months after induction of diabetes, the adrenal function of these animals was studied. Short course diabetes (5 days) was accompanied by adrenal hypertrophy and high plasma corticosterone levels; during later periods the diabetic rats consistenly showed signs of adrenal hyperactivity, yet both adrenal weight and plasma corticosterone tended to be lower than in the 5 day-treated animals. Adrenal incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
2
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 6 publications
(7 reference statements)
5
30
2
1
Order By: Relevance
“…This state can be mimicked in animals by toxic agents, such as streptozotocin (STZ) [12]. In STZ-induced DM a hyperactivity of the HPA axis was described already in 1976 [13]. Diabetes appears to be accompanied by high glucocorticoid levels, lack of circadian rhythmicity and unresponsiveness of the HPA axis to stress stimuli, especially to hypoglycemia [10, 14].…”
Section: Introductionmentioning
confidence: 99%
“…This state can be mimicked in animals by toxic agents, such as streptozotocin (STZ) [12]. In STZ-induced DM a hyperactivity of the HPA axis was described already in 1976 [13]. Diabetes appears to be accompanied by high glucocorticoid levels, lack of circadian rhythmicity and unresponsiveness of the HPA axis to stress stimuli, especially to hypoglycemia [10, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycemia is a strong stimulus for HPA axis activation and glucocorticoid production (11,19). Hyperactivity of the HPA axis in experimental STZinduced DM had already been found in 1976 (16). It is also known that patients with both types of DM can have an increased plasma cortisol level (12).…”
mentioning
confidence: 99%
“…Diabetic patients, even those with good glycemic control, demonstrate elevated levels of plasma cortisol and ACTH hormone both before and after dexamethasone suppression tests (Cameron et al 1984, Roy et al 1990). These data demonstrate that both experimental and human diabetes mellitus are accompanied by adrenocortical hyperactivity (De Nicola et al 1976). There have been few studies of adrenal medullary function in diabetic animals.…”
Section: Introductionmentioning
confidence: 93%
“…In STZ-diabetic animal models, adrenalectomy partially restores serum glucose levels and improves diabetesinduced metabolic symptoms (Rodgers et al 1994). Overproduction of adrenal corticosterone is responsible for exacerbating the hyperglycemia in insulin-dependent diabetes mellitus (IDDM) and for causing diabetes-associated growth retardation (De Nicola et al 1976, Rodgers et al 1994, Strack et al 1995. As exogenous corticosterone stimulates food intake and inhibits body-weight gain in adrenalectomized diabetic rats, it has been suggested that glucocorticoids and insulin are interacting reciprocal regulators of energy balance (Strack et al 1995).…”
Section: Discussionmentioning
confidence: 99%